Infection prevention and surgery in the pandemic era. Issue 11 (November 2021) - Umpleby, Helen; Houghton, Rebecca
Abstract: The COVID-19 pandemic has had a significant impact on surgical specialties. COVID-19 carries a significant risk to the surgical patient and the healthcare workers looking after them, with an increased incidence of pulmonary complications and mortality in patients who test positive perioperatively. Appropriate infection prevention and control measures are critical to ensure appropriate care is given and to reduce the risk of onward transmission. This article will discuss the measures that have been instigated and contributed to infection control in surgery, such as testing, patient isolation, personal protective equipment and ventilation. The COVID-19 pandemic has led to healthcare workers across many specialities working together to provide essential clinical care. This collaborative approach is critical to maintain excellent infection prevention and control practices required during this pandemic, which protect patients and preserve surgical services.